TRG-AS1 is a potent driver of oncogenicity of tongue squamous cell carcinoma through microRNA-543/Yes-associated protein 1 axis regulation. Issue 15 (2nd August 2020) - He, Shuwei; Wang, Xu; Zhang, Jingjing; Zhou, Fan; Li, Lei; Han, Xingmin
ABSTRACT: The long noncoding RNA T cell receptor gamma locus antisense RNA 1 (TRG-AS1) plays an important role in glioblastoma progression. The objective of this study was to determine the expression status of TRG-AS1 in tongue squamous cell carcinoma (TSCC). The regulatory effects of TRG-AS1 depletion on the malignant processes of TSCC cells were illustrated both in vitro and in vivo . Additionally, the precise molecular mechanisms through which TRG-AS promotes TSCC oncogenicity were investigated. TRG-AS1 expression in TSCC tissues and cell lines was detected using reverse transcription–quantitative PCR. Functional experiments including Cell Counting Kit-8 assay, flow cytometric apoptotic assay, migration and invasion assays, and xenograft tumor model analysis were conducted to severally determine the effects of TRG-AS1 on TSCC cell proliferation, apoptosis, migration, and invasion in vitro and tumor growth in vivo . Herein, TRG-AS1 was highly expressed in TSCC and closely associated with advanced TNM stage, high lymph node metastasis, and poor overall survival. Functionally, TRG-AS1 depletion suppressed TSCC cell proliferation, migration, and invasion in vitro ; promoted cell apoptosis; and attenuated tumor growth in vivo . Mechanistically, TRG-AS1 served as a molecular sponge for microRNA-543 (miR-543), thereby contributing to the increased expression of Yes-associated protein 1 (YAP1) – a miR-543 target. Rescue experiments confirmed that miR-543 inhibition or YAP1 overexpression abrogated the anticancer effects of TRG-AS1 silencing in TSCC cells. In conclusion, TRG-AS1 aggravates TSCC malignancy by regulating the miR-543/YAP1 axis. Identification of the TRG-AS1/miR-543/YAP1 regulatory pathway may provide novel insights into TSCC diagnosis, prognosis, and therapy.